Silibinin Protects Against Isoproterenol-Induced Rat Cardiac Myocyte Injury Through Mitochondrial Pathway After Up-regulation of SIRT1 - Bei Zhou; Li-Jun Wu; Lin-Hao Li; Shin-ichi Tashiro; Satoshi Onodera; Fumiaki Uchiumi; Takashi Ikejima (Elsevier, 2006)
Terminally differentiated adult injured cardiac myocytes have been used for various animal models of heart failure. It has recently been shown that isoproterenol induces injury in rat neonatal cardiac myocytes via a β-adrenergic pathway, suggesting that it might be one of the factors involved in myocardial cell injury in heart failure in vivo. In the study, silibinin, a plant flavanoid from milk thistle was first evaluated for its protective effect against β-adrenergic agonist isoproterenol-induced injury in cultured rat neonatal cardiac myocytes. The viability, activation of lactate dehydrogenase (LDH), and content of maleic dialdehyde (MDA) were chosen for measuring the degree of cardiac myocytes injury. As a result, silibinin protected isoproterenol-treated rat cardiac myocytes from death and significantly decreased LDH release and MDA production. Silibinin increased superoxide dismutase activity, decreased [Ca2+]i, and increased mitochondrial membrane potential (∆Ψ). Furthermore, the release of pro-apoptotic cytochrome c from mitochondria was reduced by silibinin. Silibinin increased the expression of anti-apoptotic Bcl-2 family protein Bcl-2, and up-regulation of SIRT1 inhibited the translocation of Bax from cytoplasm to mitochondria, which caused mitochondrial dysfunction and cell injury. These results demonstrate that silibinin protects against isoproterenol-induced cardiac myocytes injury through resuming mitochondrial function and regulating the expression of SIRT1 and Bcl-2 family members. Keywords:: silibinin, cardiac myocyte (rat), injury, mitochondrial membrane potential, SIRT1